Ultra-small angle neutron scattering and X-ray tomography studies of caseinate-hydroxyapatite microporous materials - Ritzoulis, Christos; Strobl, Markus; Panayiotou, C.; Choinka, G.; Tsioptsias, C.; Vasiliadou, C.; Vasilakos, V.; Beckmann, F.; Herzen, J.; Donath, T. (Materials chemistry and physics, 2010)
Microporous hydroxyapatite-protein composite materials of bimodal pore size distribution, intended for utilization as bone regeneration scaffolds, have been prepared by means of milk caseinate emulsion droplet templating. Ultra-small angle neutron scattering (USANS) has been utilized in order to obtain information on the size distribution of the smaller pores (less than tens of micrometers), as compared to the emulsions that have been initially used as templates. The samples were subsequently visualized in 3 dimensions using synchrotron radiation X-ray tomography, where information concerning the larger pores has been obtained. The examination of the samples confirmed a strong correlation between the size of the templating droplets and the produced pores. In addition, 1μm-sized pores appear to adhere to the surface of 20-70μm pores, providing an irregular surface on the large pore walls, a desirable feature in bone-mimicking materials.
Gesehen am 25.05.2023